Constructive Interference-Based Symbol-Level Precoding Design for Millimeter-Wave Massive Multiuser MIMO Systems With Hardware-Efficient Hybrid Precoding Architecture - Chen, Jung-Chieh (IEEE access, 2021)
This study considers the constructive interference-based symbol-level precoding design problem in millimeter-wave massive multiuser multiple-input multiple-output systems with hybrid analog-and-digital precoding architecture. In contrast to traditional hybrid precoding architecture in which the analog part is implemented by infinite-resolution phase shifters, analog precoders are achieved in this study using low-cost and energy-efficient switches and inverters. Our objective is to design a hybrid precoder that minimizes the Euclidean distance between the hybrid precoder and the optimal fully digital precoder. However, such a design problem is difficult due to the intricate coupling of digital and analog precoder variables. Thus, we apply the alternating minimization (AltMin) framework to decouple the considered problem into digital and analog precoder design problems and then solve for digital and analog precoders in an alternating manner. By adopting the AltMin framework, we obtain a closed-form solution for digital precoder. Nevertheless, solving the analog precoder design problem incurs combinatorial complexity, which we address by proposing a coordinate descent algorithm to sequentially update each element of the analog precoder with a closed-form expression. Simulation results reveal that the application of the proposed algorithm for the proposed hardware-efficient hybrid precoding architecture provides the desired balance among symbol error rate performance, power consumption, and hardware cost.